An accurate SPH Volume Adaptive Scheme for modeling strongly-compressible multiphase flows. Part 2: Extension of the scheme to cylindrical coordinates and simulations of 3D axisymmetric problems with experimental validations - Sun, P.-N.; Le Touzé, D.; Oger, G.; Zhang, A.-M. (Journal of computational physics, 2021)
•The strongly-compressible SPH model is extended to cylindrical coordinate.•A convenient and effective way of avoiding singularity at the axis is adopted.•VAS is important for both strongly- and weakly-compressible flow simulations.•Axisymmetric-SPH results are validated with 3D experimental data. The present work is dedicated to extending the strongly-compressible multiphase SPH Volume Adaptive Scheme (see [22]) from Cartesian to cylindrical polar coordinates for addressing axisymmetric problems. By omitting the gradient in the circumferential direction, an Axisymmetric-SPH model is developed. Three-dimensional axisymmetric problems including rising bubbles, expanding or collapsing bubbles are conveniently and efficiently simulated using the proposed Axisymmetric-SPH model. Contrary to the purely three-dimensional SPH model established in Cartesian coordinates, with the axisymmetric model, sufficient particle resolutions can be easily adopted to reach converged simulations of complex problems. Axisymmetric-SPH results are validated either using experimental data or other numerical results. In the Axisymmetric-SPH model, a convenient and effective way of avoiding singularity at the axis is presented. In addition, the Volume Adaptive Scheme (VAS), originally developed for compressible flow simulations with large volume variations in Cartesian coordinates, is shown to be a crucial tool to adjust particle volumes in the Axisymmetric-SPH model for all flow cases, including both weakly-compressible and strongly-compressible flows.